The Effect of Current Ratio, Price to Book Value, Net Profit Margin, Debt to Equity Ratio, and Return On Assets on Stock Prices Moderated by Earning Pershare - Hasanudin (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Using the IDX30 corporation as a control, this research sought to find out how the current ratio, price to book value, net profit margin, debt-to-equity ratio, and return on assets influenced stock prices. Secondary data was gathered from IDX and the annual report of the company for this investigation. This study uses a sample of 15 IDX30-listed firms from 2014 to 2018, and observes data from 30 other companies. Smart PLS is the analysis method employed. It has been found that stock prices are affected by the factors PBV, ROA, and CR, but NPM has no meaningful effect on stock prices. The link between CR and NPM on stock prices is unaffected by EPS, whereas EPS moderates PBV, DER, and ROA.